Patrera virgata - Oliveira, Luiz Fernando M.; Brescovit, Antonio D. (Zenodo, 2021)
Patrera virgata (Keyserling, 1891) Figs 7A–D; 27F Anyphaena virgata Keyserling, 1891: 92, fig 54 (Syntypes two males and four females from Fazenda Calvário, Serra Vermelha, Itaocara (21°40’44”S; 42°4’55”W), Rio de Janeiro, Brazil, Prof. Göldi leg., deposited in BMNH 1890.7.1.595-600, examined). Lectotype male in BMNH 1890.7.1.595 and paralectotypes one male and four females in BMNH 1890.7.1.626–630, here designated). Teudis virgatus : Petrunkevitch, 1911: 519. Patrera virgata : Brescovit, 1997: 33. Other material examined. None. Diagnosis. Patrera virgata resembles P. concolor by the male having conspicuous retrolateral tibial apophysis and flattened median apophysis in the male palp (as in Figs 17C, D, 18A, B), and having large hood and broad atrium in the female epigynum (as in Figs 17F, 18C). They differ by the inverted U-shaped sperm duct in the tegulum and by the retrolateral tibial apophysis enlarged at tip and presenting two laminar, triangular projections (Figs 7A, B) in the male palp. Females differ by the epigynum with semicircular hood and part of the copulatory ducts ventrally arched, shown by transparency (Figs 7C, D). Description. Male (Lectotype). Carapace reddish yellow with orange paramedian bands. Chelicerae, labium and endites reddish brown. Sternum and legs yellow. Abdomen yellow graying dorsally, with two blackish paramedian bands, ventrally light gray with cream spinnerets. Total length 4.8, carapace length 2.2, width 1.7. Clypeus height 0.08. Eye diameters and interdistances: AME 0.07, ALE 0.14, PME 0.14, PLE 0.15; AME–AME 0.06, AME–ALE 0.05, PME–PME 0.12, PME–PLE 0.12, ALE–PLE 0.06. Chelicerae 1.45 long, five promarginal teeth, six retromarginal denticles. Leg measurements: leg I—femur 3.0/ patella 1.0/ tibia 3.55/ metatarsus 3.15/ tarsus 1.3/ total 12.0; II—2.6/ 0.9/ 3.0/ 2.7/ 1.15/ 10.15; III—1.7/ 0.7/ 1.4/ 1.9/ 0.6/ 6.3; IV—2.5/ 0.75/ 2.4/ 3.1/ 0.65/ 9.4. Leg spination: I— II—tíbia v2-2-0, p1-1-1, r1-1-1, metatarsus v2-1-0, p1-1-1, r1-1-1; III—tibia v2-2-0, p1-1-0, r1-1-0, metatarsus v2-2-2, p1-1-1, r1-1-1; IV—tibia v2-2-1, p1-1-0, r1-1-0, metatarsus v2-2-2, p1-1-1, r1-1-1. Abdomen: length 2.70, epigastric furrow 1.3 from tracheal spiracle, spiracle 1.4 from base of spinnerets. Palp: tibia straight, slightly longer than the cymbium; cymbium oval; tegulum oval; tegular projection short, almost completely covered by the tegulum; elongated, subapical median apophysis; slender embolus, originating at the base of the tegulum (Figs 7A, B). Female (BMNH 1890.7.1.597). Colorations as in male, except abdomen lighter. Total length 5.4, carapace length 2.3, width 1.8. Clypeus height 0.06. Eye diameters and interdistances: AME 0.08, ALE 0.15, PME 0.14, PLE 0.15; AME–AME 0.05, AME–ALE 0.05, PME–PME 0.12, PME–PLE 0.12, ALE–PLE 0.06. Chelicerae 1.05 long, five promarginal teeth, six retromarginal denticles. Leg measurements: leg I—femur 2.3/ patella 0.9/ tibia 2.4/ metatarsus 2.0/ tarsus 1.0/ total 8.6; II—2.1/ 0.8/ 2.05/ 1.7/ 0.8/ 7.45; III—1.5/ 0.7/ 1.1/ 1.55/ 0.5/ 5.35; IV—2.2/ 0.8/ 1.8/ 2.4/ 0.7/ 7.9. Leg spination: I—tibia v2-2-0, p0, r0, metatarsus v2-0-0, p0, r0; II—tibia v2-2-0, p1-1-1, r0, metatarsus v2-0-0, p0, r0; III—tibia v2-1-0, p1-1-1, r1-1-1, metatarsus v2-2-2, p1-1-0, r1-1-0; IV—tibia v2-2-2, p1- 1-0, r1-1-0, metatarsus v2-2-2, p1-1-1, r1-1-1. Abdomen: length 3.0, epigastric furrow 0.9 from tracheal spiracle, spiracle 1.0 from base of spinnerets. Epigynum: lateral borders connected distally; large and deep atrium; internally with elongated, coiled copulatory ducts; elongated and globose seminal receptacles, in the proximal area of the copulatory ducts; globose spermathecae; fertilization ducts shorter than spermathecae, curved and basal (Figs 7C, D). Distribution . Known only to the type locality, in the state of Rio de Janeiro, Brazil (Fig. 27F). : Published as part of Oliveira, Luiz Fernando M. & Brescovit, Antonio D., 2021, The spider genus Patrera Simon (Araneae: Dionycha, Anyphaeninae) in the Atlantic Forest biome, with the description of one new species from Brazil, pp. 201-246 in Zootaxa 4991 (2) on pages 215-217, DOI: 10.11646/zootaxa.4991.2.1, http://zenodo.org/record/5028185 : {"references": ["Keyserling, E. (1891) Die Spinnen Amerikas. Brasilianische Spinnen. Vol. 3. Bauer & Raspe, Nurnberg, 278 pp.", "Petrunkevitch, A. (1911) A synonymic index-catalogue of spiders of North, Central and South America with all adjacent islands, Greenland, Bermuda, West Indies, Terra del Fuego, Galapagos, etc. Bulletin of the American Museum of Natural History, 29, 1 - 791. https: // doi. org / 10.5962 / bhl. title. 23819", "Brescovit, A. D. (1997) Revisao de Anyphaeninae Bertkau a nivel de generos na regiao Neotropical (Araneae, Anyphaenidae). Revista Brasileira de Zoologia, 13, 1 - 187. https: // doi. org / 10.1590 / S 0101 - 81751996000500001"]}